Preliminary prospection of phytotherapic compounds from the essential oils from barks and leaves of Umburana (Commiphora Leptophloeos) - Keyla Bessa Pinto; Pedro Henrique Batista dos Santos; Laiza Canielas Krause; Elina Bastos Caramão; Thiago Rodrigues Bjerk (Universidade de São Paulo, 2023)
Abstract The potential of the biome caatinga (exclusive from northeastern Brazil) has been evaluated in recent research for application in the pharmaceutical industry. Among the species of medicinal plants from caatinga, one can highlight the Commiphora leptophloeos (umburana), which has been used as infusions and syrups by the regional population for inflammatory and infectious diseases. Essential oils from umburana leaves and barks were obtained in a Clevenger apparatus and analyzed by gas chromatography/mass spectrometry, and total phenolic and flavonoids were determined by spectrophotometric analysis. It was observed that a large part of the major compounds present in the essential oil is described as having antitumor activity, enabling research in investigational oncology with umburana (C. leptophloeos). In addition, some little explored components have been identified, such as cadinene, alpha-selinene, and elemenone. Despite being easily found in several plants, there are no clinical trials involving their biological activity in a well-defined isolated form, which could make exploring new studies possible. Furthermore, the presence of phenolic compounds and flavonoids allows future studies about the potential antimicrobial and antioxidant activity.